Implementasi Kegiatan Ekstrakurikuler Hadrah terhadap Pembentukan Karakter Religius Peserta Didik di Madrasah Ibtidaiyah - Bayhaki, Rosi; Yanuardianto, Elga; Ulfa, Maria (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Hadrah extracurricular is one of the activities that helps the formation of religious character in schools. Through this activity, it is hoped that the religious character of each student can be formed. 1) The formulation of the objectives of the hadrah extracurricular activity program aims to enable students to have an Islamic artistic soul and be able to achieve a religious personality or good character according to Islamic teachings. The selection of the hadrah extracurricular activity program is carried out once a year which is attended by the head of the foundation, the principal, and teachers/staff/employees. Identification and direction of sources are carried out so that students have an Islamic artistic soul, a good religious character, and are qualified in terms of their knowledge. 2) The role of hadrah extracurricular activities in the formation of the religious character of students at MIMA Condro Jember is that hadroh is an entry point for today's people to know religion. So it can change bad speech into good, and also people who participate in hadrah tend to be close to people who understand religion. Hadrah extracurricular activities can also shape students' religious character, such as strong faith, consistency in worship, purification of the soul (Tazkiyatun Nafs), noble morals, social responsibility, knowledge, and good deeds.